2019
DOI: 10.1101/730457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global transcriptomic profiling of the bone marrow stromal microenvironment during postnatal development, aging and inflammation

Abstract: Bone marrow (BM) stromal cells provide the structural and regulatory framework for hematopoiesis and contribute to developmental-stage specific niches, such as those preserving hematopoietic stem cell (HSCs). Despite recent advances in our understanding of stromal composition and function, little is known on the dynamic transcriptional remodeling that this compartment undergoes over time and during adaptation to stress. Similarly, how molecular changes in stroma are linked to age-related modulation of hematopo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 115 publications
(135 reference statements)
3
33
0
Order By: Relevance
“…These findings highlight the differential effects between transient and prolonged IL-10 perturbations on stroma. Our observations suggest that acute perturbations of Tregs/IL-10, as seen with anti-CD25, IL-10R blockage, and FTY720, lead to increased stromal proliferation, consistent with a stress response (80). Conversely, lifelong loss of IL-10 signaling, as seen with genetic deletions, appears to hamper stromal cell maturation, resulting in decreased numbers.…”
Section: Resultsmentioning
confidence: 52%
“…These findings highlight the differential effects between transient and prolonged IL-10 perturbations on stroma. Our observations suggest that acute perturbations of Tregs/IL-10, as seen with anti-CD25, IL-10R blockage, and FTY720, lead to increased stromal proliferation, consistent with a stress response (80). Conversely, lifelong loss of IL-10 signaling, as seen with genetic deletions, appears to hamper stromal cell maturation, resulting in decreased numbers.…”
Section: Resultsmentioning
confidence: 52%
“…Niche cell populations may regulate the hematopoietic response to peripheral inflammation or infection, for instance, by releasing factors that promote myelopoiesis ( 5 , 32 , 33 ) ( Figure 2A ). Such a factor is granulocyte colony-stimulating factor (G-CSF), a central regulator of infection-induced emergency granulopoiesis, as it exerts a key role in the differentiation of progenitors of the myeloid lineage to mature granulocytes ( 5 ).…”
Section: Hsc Niche Adaptation To Inflammationmentioning
confidence: 99%
“…Another study demonstrated that treatment of mice with IFN-α or polyinosinic:polycytidylic acid (polyI:C) activates BM endothelial cells and increases vascularity and vessel permeability ( 49 ). Moreover, single-cell transcriptomic analysis revealed that the administration of polyI:C and LPS induces gene expression of the chemokines Ccl5, Ccl6, Ccl19, Cxcl9, Cxcl10 , and Cxcl11 in CXCL12-abundant reticular cells and sinusoidal endothelial cells ( 32 ). Additionally, inflammation induced the expression of Il6 and downregulated the expression of factors that contribute to HSC retention and lymphopoiesis, including Cxcl12, Kitl , and Il7 ( 32 ).…”
Section: Hsc Niche Adaptation To Inflammationmentioning
confidence: 99%
“…Together with metabolic and epigenetic shifts, the composition of supporting cells and the levels of secreted factors in the BM microenvironment change with age ( Mendelson and Frenette, 2014 ; Verovskaya et al., 2019 ). Detected both systemically and in the BM stroma, inflammation is an important event during aging and can alter hematopoiesis ( Kovtonyuk et al., 2016 ; Helbling et al., 2019 ). As inflammation can contribute to cancer pathogenesis, one possible explanation for the development of DDL from CHIP donors is that hematopoietic lineages exhibiting pro-inflammatory phenotypes may modify the BM microenvironment and hematopoiesis to promote leukemogenesis ( Figure 2 ) ( Henry et al., 2015 ; Leimkuhler and Schneider, 2019 ).…”
Section: Main Textmentioning
confidence: 99%